Analisis Kesehatan Lingkungan di Tebet Eco Park dalam Mendukung Kesehatan Masyarakat Perkotaan - Nurul Aisyah; Fauziyah Nur Irbah; Syalsabillah Alamsyah; Nasywa Mahesa (STIKES Columbia Asia Medan, 2026)
Tebet Eco Park is one of the green open spaces (GOS) in South Jakarta that plays an important role in supporting environmental health and urban public health. This study aims to analyze the environmental health conditions at Tebet Eco Park through direct observation of environmental cleanliness, air quality, water quality, waste management, sanitation facilities, and visitor comfort. The research employed a descriptive method using field observations and a literature review approach. The findings indicate that the overall environmental health condition of Tebet Eco Park is relatively good. The presence of diverse vegetation contributes to improving air quality and creating a cool and comfortable environment. Supporting facilities such as sports areas, playgrounds, pet-friendly zones, and drinking water refill stations also contribute to the physical and social well-being of the community. However, several issues were still identified, including poor water quality in the park’s ponds and improper waste disposal by some visitors. Therefore, more effective environmental management and increased public awareness are needed to ensure that the ecological and social functions of Tebet Eco Park can be sustained in the long term.